The Influence of Performance Expectancy, Effort Expectancy, and Social Influence of Sharia Stock Application Technology on the Interest in Sharia Stock Investment in Medan City with Sharia Insight as a Moderating Variable - Hutabarat, Sauril Rahmadi; Yafiz, Muhammad; Arif, Muhammad (UNIVERSITAS PAKUAN, 2025)
This study analyzes the influence of sharia stock investment technology on investment interest in Medan City using the UTAUT model and adding sharia insights as a moderating variable. The method used is quantitative analysis using SEM-PLS on 160 respondents who are sharia stock investors. The results show that performance expectancy, effort expectancy, and social influence significantly affect investment interest. Sharia insights also have a direct positive impact and significantly moderate the influence of effort expectancy and social influence on interest, but not on performance expectancy. These findings emphasize the importance of technological ease and religious understanding in encouraging interest in sharia investment. The development of platform features and early financial literacy, particularly related to Islamic principles, is recommended to enhance participation. This study expands the application of UTAUT by highlighting the role of religious literacy in technology acceptance.